The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/cnma.202000005
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid‐Intercalated Metallic MoS2 as a Superior Electrode for Energy Storage Applications

Abstract: The development of MoS2 in the metallic phase (1T‐MoS2) is of paramount interest as it exhibits superior electrochemical activities compared to its semiconducting polymorph (2H‐MoS2). In this work, an ionic liquid (IL)‐assisted solvothermal method was employed to produce the thermodynamically metastable 1T‐MoS2. Structural characterization of the material suggests the intercalation of the IL into MoS2. De‐intercalation of ILs from 1T‐MoS2 leads to the formation of 2H‐MoS2. Carbon cloth‐supported 1T‐MoS2(1T‐MoS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 54 publications
(145 reference statements)
7
29
0
Order By: Relevance
“…The gravimetric capacitance is of the same magnitude as the ILs-intercalation 1T-MoS 2 electrode used in the previous experiment (18 F g −1 ). [28] In particular, in this experiment, the interlayer spacing, obtained by [Emim] + insertion, is 1.006 nm, close to the simulation result (1.115 nm). The volumetric capacitance is also at the same magnitude with an experiment that 250 F cm −3 was obtained of a 1T-MoS 2 electrode with [Emim][BF 4 ]/ACN, [18] indicating that the simulation and experiment could be in agreement for comparison.…”
Section: Differential Capacitance and Interlayer Il Structuresupporting
confidence: 86%
See 1 more Smart Citation
“…The gravimetric capacitance is of the same magnitude as the ILs-intercalation 1T-MoS 2 electrode used in the previous experiment (18 F g −1 ). [28] In particular, in this experiment, the interlayer spacing, obtained by [Emim] + insertion, is 1.006 nm, close to the simulation result (1.115 nm). The volumetric capacitance is also at the same magnitude with an experiment that 250 F cm −3 was obtained of a 1T-MoS 2 electrode with [Emim][BF 4 ]/ACN, [18] indicating that the simulation and experiment could be in agreement for comparison.…”
Section: Differential Capacitance and Interlayer Il Structuresupporting
confidence: 86%
“…IL molecules into the MoS 2 layers led to an enhanced interlayer spacing (~1 nm) with the generation of conducting basal planes, which exhibits superior electrochemical properties. [28] Geng et al synthesized pure 1T-MoS 2 combined with an inserted monolayer of water, which results in an interlayer spacing of 1.18 nm, and utilized it for supercapacitor application. [23] They found that the capacitance of such a supercapacitor could reach 380 F g −1 in aqueous Li 2 SO 4 solution, and 88% of specific capacitance remained after 10 000 cycles at 5 A g −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the improved activity of the 1T/2H−MoSe 2 (2 Cr) is attributed to the conducting basal planes, high 1T phase content and the presence of additional active sites. The ECSA normalized polarization curves provide the insight about the per site catalytic activity [29] . Interestingly, the per site activity of 1T/2H−MoSe 2 (2 Cr) is lower compared to the 2H−MoSe 2 (Figure S7) which further complements the fact that the improved electrocatalytic activity of 1T/2H−MoSe 2 (2 Cr) is due to the presence of more number of active sites.…”
Section: Resultsmentioning
confidence: 77%
“…Similarly, the insertion of oxidized DMF species into MoS 2 layers also could stabilize the 1T phase [28] . Recently, we have shown that intercalation of ionic liquids into MoS 2 can stabilize the 1T phase MoS 2 [29] …”
Section: Introductionmentioning
confidence: 94%
“…Molybdenum disulfide is a layered van der Waals solid with remarkable properties tunable for nanoelectronics, energy storage and catalysis [1–5] . Two kinds of MoS 2 layer structures are known, with the trigonal‐prismatic (called 2H) and octahedral (1T) coordination surrounding of Mo with S in the S−Mo−S sandwich‐like layers, resulting to semiconducting stable material or its metallically conducting metastable counterpart, respectively [6,7] .…”
Section: Introductionmentioning
confidence: 99%